Use Of Image Media To Improve Learning Performance - Dwi Kurniawati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to find out whether the application of learning with images can improve learning achievement. This research is in the form of stages which are recycling processes starting from the stages of planning, implementing actions, observations, and reflections. From the stages of activity obtained the following results: Early stage, the process of learning outcomes of children 47% of which all in the initial condition is only 40%. This is due to: (a) Many students are silent and passive; (b) The teacher's voice is less clear. At the final stage, with pictures and microphones, student learning outcomes increase to 80% as expected. This is due to: (a) Use of images; (b) Use of microphones. From the results of the analysis can be concluded through the use of images can increase learning achievement. Suggestions that the author can convey, to colleagues: (a) Choose the right learning strategy; (b) Experience in this research activity should motivate fellow teachers to conduct research.